Initial CT scanning in patients with COVID-19 pneumonia in the peruvian central air force hospital: a case series - Cáceres-Bernaola, Ursula (2020)
We present nine cases of COVID-19 patients that developed pneumonia caused by SARSCov-2 who were seen in the Peruvian Central Air Force Hospital and showed different clinical features, risk factors, and outcomes. Findings of their thorax CT scans are described using a tomographic score that was applied on admission. Points assigned were based on the percentage of involvement on each pulmonary lobe and this allowed us to determine a clinical diagnosis of pneumonia according to its severity, even before having positive results in molecular and serological tests for some of these patients.